2008
DOI: 10.1001/archpedi.162.7.675
|View full text |Cite
|
Sign up to set email alerts
|

Primary Early Thoracoscopy and Reduction in Length of Hospital Stay and Additional Procedures Among Children With Complicated Pneumonia

Abstract: Our large retrospective multicenter study demonstrates that, compared with primary chest tube placement, primary VATS is associated with shorter LOS and fewer additional procedural interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 40 publications
3
26
1
5
Order By: Relevance
“…The authors of these studies concluded that, despite the small sample sizes, the lack of significant differences indicates that the interventions are equally effective. These findings contradict the findings of previous retrospective studies, but those likely were influenced by case selection bias [21,22].…”
contrasting
confidence: 97%
“…The authors of these studies concluded that, despite the small sample sizes, the lack of significant differences indicates that the interventions are equally effective. These findings contradict the findings of previous retrospective studies, but those likely were influenced by case selection bias [21,22].…”
contrasting
confidence: 97%
“…Many authors have suggested that thoracoscopy is more advantageous as the initial treatment than tube thoracostomy alone [17][18][19]. Shah's multicenter study supports the early use of thoracoscopy, pointing to shorter hospital stays and fewer instances of further surgery [20]. Indeed, the separation and washing out of the septa allows for better visibility inside the thoracic cavity and more efficient expansion of the affected lung [21].…”
Section: Dctd -Duration Of Chest Tube Drainage; Los -Length Of Staymentioning
confidence: 99%
“…A series of studies began to emerge analyzing data from large administrative datasets that described the variation in hospital care (but lack clinical results and clinical outcomes outside of the hospital setting), such as the Pediatric Health Information Systems (PHIS) database operated by the Children's Hospital Association (formerly known as the Child Health Corporation of America). [9][10][11][12][13] Pediatric hospital medicine fellowships began to appear, 14 and over time, a cohort of hospitalist investigators with sufficient independence to mentor others arose.…”
Section: Hospital Medicine Research: Growth and Developmentmentioning
confidence: 99%